2022
DOI: 10.3390/healthcare10091691
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and Change in Physical Activity and Physical Fitness across Four Years of College Students after One Year of COVID-19 Lockdown

Abstract: The relationship between physical activity (PA) and physical fitness (PF) has been well established among college students. However, the impact of this relationship after 1 year of COVID-19 pandemic lockdown measures is unclear. This study aimed to test the relationship between PA and PF, exploring the trend across four years, the different components of PF related to PA, and their determinants, by analyzing specific items. A total of 1506 university students (19.48 ± 1.35 years old, 55.8% male) in years 1–4 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The decline in fitness observed in our study is potentially due to a combination of disrupted physical activity routines, altered dietary habits, and pandemic-induced psychological stressors. Measures implemented to mitigate the spread of COVID-19 resulted in a significant disruption of daily life, including the closure of recreational and exercise facilities, which in turn led to reduced physical activity levels and increased sedentary behaviour 13 , 29 . This effect was particularly pronounced in areas with higher deprivation levels and among individuals who were previously inactive 6 , 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decline in fitness observed in our study is potentially due to a combination of disrupted physical activity routines, altered dietary habits, and pandemic-induced psychological stressors. Measures implemented to mitigate the spread of COVID-19 resulted in a significant disruption of daily life, including the closure of recreational and exercise facilities, which in turn led to reduced physical activity levels and increased sedentary behaviour 13 , 29 . This effect was particularly pronounced in areas with higher deprivation levels and among individuals who were previously inactive 6 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Although qualitative research has provided valuable insights into how individuals’ behaviours might be affected by the pandemic and lockdowns, it falls short of providing an accurate representation of fitness changes compared with objective measurements. Recent research by Yu et al suggested that changes in physical activity over time could be associated with decreased fitness after the pandemic, however, this study only offers a snapshot in time as it lacks baseline data from before the pandemic 13 . Lastly, a prevalent issue in the existing evidence is the lack of control groups in studies involving young adult populations, significantly limiting the strength of the evidence 14 , 15 .…”
Section: Introductionmentioning
confidence: 97%
“…They relied on the Intuitive Exercise Scale to determine the most prominent dimensions of exercise during the pandemic, and they found that exercising for fun, exercising to influence emotions, and loss of motivation to exercise were the emerging themes. Yu et al [ 29 ] tested the relationship between PA and fitness in 1505 university students after one year of the COVID-19 lockdown using the International Physical Activity Questionnaire (Chinese version) and selected fitness measures according to gender. A comparison of the measures taken before (annually for three years) and during the COVID-19 pandemic (fourth year) revealed a significant decline in PA levels in females and a decline in overall physical fitness in both males and females.…”
Section: Introductionmentioning
confidence: 99%
“… 52 However, our study had a large percentage of high-intensity PA (82.3%); this may be due to the large size of the school, where bicycles are the primary mode of transport and students need to cycle quickly between buildings every day. At the same time, our school’s physical education classes require students to run at least 2 km after school every day, which counts as 10 points towards their physical education grade; 53 this is a characteristic of the PA variable for college students in our model.…”
Section: Discussionmentioning
confidence: 99%